Analisis Manajemen Pemeliharaan Sarana dan Prasarana di Rumah Sakit Umum Daerah Rokan Hulu - Hendrisman; Sumengen Sutomo; Arnawilis Arnawilis; Budi Hartono; Lita Lita (Jurnal Kesehatan Komunitas, 2021)
Hospital Infrastructure Maintenance Installation is a functional unit to carry out activities, so that the facilities that support health services in the hospital, namely facilities, infrastructure and equipment are always in a functioning state and fit for use. Management of facilities and infrastructure still lacks of manpower. The placement of human resources is not right, there is still a lack of training on personnel and the maximum budget is not yet available. The purpose of this study was to determine the system for maintaining the facilities and infrastructure in RSUD Rokan Hulu, Riau Province. This research is a descriptive analysis with qualitative methods. The number of informants in this study was 9 people consisting of 4 main informants and 5 supporting informants. The instrument used by conducting in-depth interviews, observation and document review. The results of this study indicate that the implementation of the hospital maintenance management system has not been carried out properly, due to limited technicians, lack of technical and managerial training, funds are still not maximally used, infrastructure facilities still do not meet the needs for space, function and area, SPO already exists but still incomplete. Inadequate planning, organization and supervision, especially the preventive maintenance system, are not yet running well. It is hoped that hospital management can improve the system for optimal maintenance of hospital infrastructure , it is necessary to carry out technical and managerial training, complete adequate preventive and corrective maintenance facilities, increase the allocation of maintenance funds, carry out routine and scheduled preventive maintenance and complete documents in the form of policies hospital maintenance guides and guidelines